Effect Of Aggregate Grain Size Distribution On Properties Of Permeable Concrete - Yazici, ş.; Mardani-aghabaglou, A. (University of Eloued جامعة الوادي, 2017)
In this study, the effect of aggregate grain size distribution and water/cement (W/C) ratio on the mechanical properties of permeable concrete is investigated. The aim of this study is to prepare permeable concrete mixture with optimum properties in terms of strength and permeability. For this purpose, five different permeable concrete mixtures with 0.3 constant W/C ratio and containing different proportions of coarse aggregate which are 5-15 and 15-25 mm, but containing no fine aggregate are prepared. In addition, three different concrete mixtures with 0.35 W/C ratio and containing 20% (by weight) fine aggregate and different proportions of coarse aggregate which are 5-15 mm and 15-25 mm are prepared. Afterwards, some tests related to the compressive strength, splitting tensile strength, flexural strength, ultrasonic pulse velocity (UPV) and permeability of concrete mixtures are conducted. Test results demonstrate that permeability, strength and UPV of the mixtures increased upon using 20 wt% of fine aggregate instead of coarse aggregate and upon reducing coarse aggregate grain diameter though W/C ratio of mixtures increases from 0.3 to 0.35.
Article in Journal of Fundamental and Applied Sciences Vol 09, N 01
Keywords: Permeable concrete, permeability, compressive strength, splitting tensile strength, flexural strength, ultrasonic pulse velocity